Prevalence and associated factors of resting electrocardiogram abnormalities among systemic lupus erythematosus patients without cardiovascular disease - Al Rayes, Hanan (Arthritis Res Ther, 2017)
BACKGROUND: Electrocardiogram (ECG) cardiovascular disease (CVD) abnormalities (ECG-CVD) are predictive of subsequent CVD events in the general population. Systemic lupus erythematosus (SLE) patients are vulnerable to CVD. We aimed to determine the prevalence of ECG-CVD in SLE patients and to examine the risk factors associated with ECG-CVD. METHODS: A 12-lead resting supine ECG was performed on consecutive adult patients attending the clinic. One cardiologist interpreted the ECGs. ECG-CVD were defined as the presence of one or more of the following 4 elements (ECG-4): ST-segment and/or T-wave abnormalities, left ventricular hypertrophy (LVH), left axis deviation (LAD), left bundle branch block (LBBB) and right bundle branch block (RBBB). ECG-5 included the same elements as ECG-4 and the Q-wave. Repeated measurement data were created and the associations between ECG-4/ECG-5 and demographics were evaluated with univariate and multivariate Cox regression models. RESULTS: Of 487 SLE patients, 104 (21.4%) and 118 (24.2%) patients had one or more of the ECG-4 and ECG-5 elements, respectively. A higher prevalence of ECG-CVD was found in patients with a longer SLE disease duration, and the burden of ECG-CVD elements increased with age. Increased age, active SLE disease, and damage were associated with ECG4 and ECG-5, while treatment of hyperlipidemia was protective. CONCLUSION: A high prevalence of ECG-4 (21.4%) and ECG-5 (24.2%) was found in this SLE cohort. Controlling SLE disease activity is important since it was associated with ECG-4 and ECG-5. Early identification of ECG-4 and ECG-5 in SLE patients might allow for better stratification and risk management.